Constrained controllability of dynamic systems - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
The present paper is devoted to a study of constrained controllability and controllability for linear dynamic systems if the controls are taken to be nonnegative. By analogy to the usual definition of controllability it is possible to introduce the concept of positive controllability. We shall concentrate on approximate positive controllability for linear infinite-dimensional dynamic systems when the values of controls are taken from a positive closed convex cone and the operator of the system is normal and has pure discrete point spectrum.
Keywords: constrained controllability; infinite-dimensional systems; distributed-parameter systems; positive dynamic systems